Expression of NAD(P)H quinone dehydrogenase 1 (NQO1) is increased in the endometrium of women with endometrial cancer and women with polycystic ovary syndrome. (18th August 2017) - Atiomo, William; Shafiee, Mohamad Nasir; Chapman, Caroline; Metzler, Veronika M.; Abouzeid, Jad; Latif, Ayşe; Chadwick, Amy; Kitson, Sarah; Sivalingam, Vanitha N.; Stratford, Ian J.; Rutland, Catrin S.; Persson, Jenny L.; et al.
Summary: Objective: Women with a prior history of polycystic ovary syndrome (PCOS) have an increased risk of endometrial cancer (EC). Aim: To investigate whether the endometrium of women with PCOS possesses gene expression changes similar to those found in EC. Design and Methods: Patients with EC, PCOS and control women unaffected by either PCOS or EC were recruited into a cross‐sectional study at the Nottingham University Hospital, UK. For RNA sequencing, representative individual endometrial biopsies were obtained from women with EC, PCOS and a woman unaffected by PCOS or EC. Expression of a subset of differentially expressed genes identified by RNA sequencing, including NAD(P)H quinone dehydrogenase 1 ( NQO1 ), was validated by quantitative reverse transcriptase PCR validation (n = 76) and in the cancer genome atlas UCEC (uterine corpus endometrioid carcinoma) RNA sequencing data set (n = 381). The expression of NQO1 was validated by immunohistochemistry in EC samples from a separate cohort (n = 91) comprised of consecutive patients who underwent hysterectomy at St Mary's Hospital, Manchester, between 2011 and 2013. A further 6 postmenopausal women with histologically normal endometrium who underwent hysterectomy for genital prolapse were also included. Informed consent and local ethics approval were obtained for the study. Results: We show for the first that NQO1 expression is significantly increased in the endometrium of women with PCOS and EC. Immunohistochemistry confirms significantly increased NQO1 protein expression in EC relative to nonmalignant endometrial tissue ( P < .0001). Conclusions: The results obtained here support a previously unrecognized molecular link between PCOS and EC involving NQO1.